Pengembangan Media Komik untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Ais Rosyida (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2019)
The research aims to develop and test the validity, practicality, as well as the effectiveness of learning media, that is comic media on Social Science subject. Observation model used is the research and development model (R&D) of Borg and Gall. The result of this research shows that comic media is reasonable, practical and effective. The using of comic media gives influence to the learning result of student. It can be seen through the result of t-test trial which shows that tcount is 2.55 > from ttable 2.903. The using of comic media also gets good response from the students, that is 90.5%. Therefore, it can be concluded that comic media is reasonable, practical and effective to improve the learning result on Social Science subject of third grade students in Elementary School. Keyword : Comic media learning, development, learning result , Social Studies